2016
DOI: 10.1111/jdv.13991
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and dermoscopic clues to differentiate pigmented nail bands: an International Dermoscopy Society study

Abstract: Dermoscopic examination of longitudinal melanonychia provides useful information that could help clinicians to improve melanoma recognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
3
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 13 publications
1
59
3
2
Order By: Relevance
“…To overcome these limitations and increase the accuracy of diagnosis, the International Study Group on Melanonychia published official consensus statements with over a dozen diagnostic pearls based on dermoscopic images of the nail plate and hyponychium . In 2016, the International Dermoscopy Society reported clinical and dermoscopic clues to differentiate pigmented nail bands . Based on their original study, melanoma cases were significantly associated with six features: (i) width of the pigmented band of more than two‐thirds of the nail plate; (ii) gray and black coloration; (iii) irregularly pigmented lines; (iv) Hutchinson's and micro‐Hutchinson's signs; (v) nail dystrophy; and (vi) granular pigmentation.…”
Section: Dermoscopic Features Of Adult Melanonychiamentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome these limitations and increase the accuracy of diagnosis, the International Study Group on Melanonychia published official consensus statements with over a dozen diagnostic pearls based on dermoscopic images of the nail plate and hyponychium . In 2016, the International Dermoscopy Society reported clinical and dermoscopic clues to differentiate pigmented nail bands . Based on their original study, melanoma cases were significantly associated with six features: (i) width of the pigmented band of more than two‐thirds of the nail plate; (ii) gray and black coloration; (iii) irregularly pigmented lines; (iv) Hutchinson's and micro‐Hutchinson's signs; (v) nail dystrophy; and (vi) granular pigmentation.…”
Section: Dermoscopic Features Of Adult Melanonychiamentioning
confidence: 99%
“…18 In 2016, the International Dermoscopy Society reported clinical and dermoscopic clues to differentiate pigmented nail bands. 19 Based on their original study, melanoma cases were significantly associated with six features: (i) width of the pigmented band of more than two-thirds of the nail plate; (ii) gray and black coloration; (iii) irregularly pigmented lines; (iv) Hutchinson's and micro-Hutchinson's signs;…”
Section: Dermoscopic Features Of Adult Melanonychiamentioning
confidence: 99%
“…The conditions in which dermoscopy is not performable are thickened nails, blurred borders of the lesions, and a totally black nail plate [34]. A recent study [35] demonstrated a strong association between clinical and dermoscopic findings in nail band pigmentation, helping to distinguish whether a band is benign or malignant. The authors identify 3 important dermoscopic patterns that could help in this distinction: (1) the width of the band, involving more than two-thirds of the nail plate in melanoma; (2) the presence of a gray-to-black color; and (3) the presence of nail dystrophy, which increases the risk of detecting a nail melanoma 3 times.…”
Section: Alterations Of the Nail Platementioning
confidence: 99%
“…However, this has not been validated in children and may not be representative due to differences in nail plate size. It has been suggested that a more accurate measure may be grouping the width of pigmentation into three groups: less than 1/3, between 1/3 and 2/3, and more than 2/3 of the width of the nail . Most subungual melanomas involve more than 2/3 of the nail plate.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that a more accurate measure may be grouping the width of pigmentation into three groups: less than 1/3, between 1/3 and 2/3, and more than 2/3 of the width of the nail. 11 Most subungual melanomas involve more than 2/3 of the nail plate. This method remains to be validated in children.…”
Section: Discussionmentioning
confidence: 99%